2020
DOI: 10.30605/25409190.167
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Taking TOEIC Test and How to Overcome: Perception of Indonesian Vocational Students

Abstract: The purpose of this research was to discover problems that Indonesian Vocational Students are having with the Test of English for International Communication (TOEIC) to improve TOEIC instruction. The participants were 18 students in school attending the TOEIC preparation course in the TOEIC course in October 2018. There were two steps in taking the data: (1) questionnaires on the listening and reading problems in the TOEIC test, and (2) interview on how they cope with the problems. The result shows that: 1) Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
1
9
0
Order By: Relevance
“…The data was analyzed qualitatively since the result needs to be present the detail description of pre-service teacher's perception. This is in line with other researchers whose employed a qualitive approach to analyze student's perceptions [33]. The description can very helpful for potraying the participant's strategies and their preparation in building an active learning environment.…”
Section: Methodssupporting
confidence: 85%
“…The data was analyzed qualitatively since the result needs to be present the detail description of pre-service teacher's perception. This is in line with other researchers whose employed a qualitive approach to analyze student's perceptions [33]. The description can very helpful for potraying the participant's strategies and their preparation in building an active learning environment.…”
Section: Methodssupporting
confidence: 85%
“…TOEIC is also utilized for job applications, and many educational institutions, particularly vocational schools and polytechnics, incorporate this standardized test as part of their graduation requirements. Zahruni et al (2020) add that the majority of schools in Indonesia, including vocational schools, use this test. Therefore, TOEIC is designed for non-native English speakers to assess their communication skills in English for business, trade, and industry (Dari & Zasrianita, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to (Fauziati, 2016), the TOEIC is specifically designed to measure English language abilities for everyday communication in international work environments. Currently, implementing English language tests in schools or educational institutions is an effective strategy for improving students' English language skills as it serves as a benchmark for researchers and workers worldwide (Zahruni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their research findings reflect the test user important segment. Zahruni, Fahmi & Pratolo (2020) examined Indonesian vocational students' perception of taking the TOEIC test and revealed that the students prepared for the test by self-learning, by having discussions with peers and by practicing online.…”
Section: Toeic English Proficiency Testmentioning
confidence: 99%